Response Of Chilli (Capsium annuum L.) To Zinc And Boron Application (Bangladesh Journal of Agricultural Research, 2013)
Field trial on chilli (cv. Bogra local) was conducted in Grey Terrace Soil under AEZ-25 (Level Barind Tract) at Spice Research Centre, Bogra during rabi seasons of 2005-2006, 2006-2007 and 2007-2008. The objectives were to evaluate the response of chilli to zinc and boron and to find out the optimum dose of zinc and boron for maximizing the yield. Treatments for this study comprised of four levels each of zinc (0, 1.5, 3.0, and 4.5 kg/ha) and boron (0, 1.0, 2.0, and 3.0 kg/ha) along with a blanket dose of N130 P60 K80 S20 Mg10 kg/ha. The experiment was set up in a randomized block design (factorial) with 3 replications. The integrated use of zinc and boron was found superior to their single applications. The interaction effect between zinc and boron was significant in case of yield of dry chilli and weight of ripe chilli/plant. The highest yield (1138 kg/ha) was recorded from Zn3B1 kg/ha, which was closely followed by Zn3B2, Zn4.5B2 and the lowest (703 kg/ha) in control (Zn0B0). The yield benefit over control varied from 4.4 to 61.9 % due to interaction effect. Consecutive three years studies showed almost similar trend of results. However, from regression analysis, the optimum-economic dose of zinc was found to be 3.91 kg/ha whereas it was 1.70 for boron. Hence, a package of (Zn3.91 B1.70 kg/ha) along with the said blanket dose may be recommended for maximizing the yield of chilli in the study area. Bangladesh J. Agril. Res. 38(1): 49-59, March 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i1.15189